1993
DOI: 10.1161/01.atv.13.4.482
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-pathological comparison of the human arterial wall. Verification of intima-media thickness.

Abstract: Recent intravascular ultrasound experience challenges the accuracy of ultrasonic measurement of arterial wall thickness. We reevaluated the correlation between histological and sonographic measurements of intima-media thickness using standard transcutaneous vascular technology. Carotid and femoral arterial segments were imaged before and after fixation using a 7-MHz linear-array vascular transducer. Log compression and beam orientation were varied. Mean intima, media, and adventitia thicknesses were measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
173
0
15

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(199 citation statements)
references
References 13 publications
(16 reference statements)
11
173
0
15
Order By: Relevance
“…Histological studies have shown that quantification of the intima-media thickness in the far wall of arteries by ultrasonography corresponds well with the true histological thickness. 13,15 The results of the present study and numerous other studies showed clear relationships between ultrasonographically determined intima-media thickness in the carotid and femoral artery and exposure to the established risk factors of atherosclerosis, such as arterial hypertension and hypercholesterolemia, even in young individuals. 16 -19 Furthermore, it has been shown that intima-media thickness of the carotid and femoral artery is a good indicator of atherosclerotic lesions in the coronary and peripheral arteries.…”
Section: Discussionsupporting
confidence: 75%
“…Histological studies have shown that quantification of the intima-media thickness in the far wall of arteries by ultrasonography corresponds well with the true histological thickness. 13,15 The results of the present study and numerous other studies showed clear relationships between ultrasonographically determined intima-media thickness in the carotid and femoral artery and exposure to the established risk factors of atherosclerosis, such as arterial hypertension and hypercholesterolemia, even in young individuals. 16 -19 Furthermore, it has been shown that intima-media thickness of the carotid and femoral artery is a good indicator of atherosclerotic lesions in the coronary and peripheral arteries.…”
Section: Discussionsupporting
confidence: 75%
“…26 An RMI 413 tissue-mimicking phantom was used to monitor instrument performance. Three segments were defined: the distal 10 mm of the common carotid artery, the carotid bifurcation from the widening of the artery up to the flow divider, and the proximal 10 mm of the internal carotid artery.…”
Section: Ultrasound Outcome Measuresmentioning
confidence: 99%
“…Three segments were defined: the distal 10 mm of the common carotid artery, the carotid bifurcation from the widening of the artery up to the flow divider, and the proximal 10 mm of the internal carotid artery. Only measurements of the wall far from the probe were considered for calculation of outcome measures, for 2 reasons: ultrasound measurement of the near wall underestimates the true histological thickness, 26 and the visualization of the near wall was often not possible in sufficient quality, as has been reported from other trials. 27 Subjects were examined supine with a small pillow under the neck.…”
Section: Ultrasound Outcome Measuresmentioning
confidence: 99%
“…Atherosclerosis was measured as thickness of the intimal and medial layers of the artery as visualized by high-resolution 7.5 MHz ultrasound (Apogee CX Color; ATL, Bothel, WA, USA) [15]. An RMI 413 tissue-mimicking phantom was used to monitor instrument performance.…”
Section: Ultrasound Outcome Measuresmentioning
confidence: 99%
“…The examination was repeated at study end according to the same protocol, using the same angles of interrogation. Only the far wall was considered for calculation of outcome measures since ultrasound measurement of the near wall underestimates the true histological thickness and proper visualization is often difficult [5,15]. The measurement of the carotid IMT has been described previously [7].…”
Section: Ultrasound Outcome Measuresmentioning
confidence: 99%